2009
DOI: 10.1386/ac.20.2.193_1
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Proximity and Distance: The Reception of Korean Films in China Through the Lens of My Sassy Girl

Abstract: This article explores the reception of Korean romantic comedy, My Sassy Girl, among Chinese youth. Through the lens of this popular movie, the authors attempt to explain the complexity of the popularity of Korean films and other cultural products in China in recent years. By analyzing the outcome of online questionnaires and depth interviews regarding the reception of My Sassy Girl, the authors argue that although the strong presence of Korean films in China is contributed by the significant growth of the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…e impact of cultural proximity on audience attitudes towards foreign films has been examined in numerous previous cross-cultural studies. For instance, scholars have shown that cultural proximity predicts the popularity of Korean movies and TV dramas among Chinese audiences [28,29] and Asian films among Malaysian audiences [10,30]. Straubhaar's [20] argument also provides a theoretical underpinning that enables an assessment of the extent to which Korean dramas are culturally acceptable to other Asian countries [11].…”
Section: Cultural Proximitymentioning
confidence: 99%
“…e impact of cultural proximity on audience attitudes towards foreign films has been examined in numerous previous cross-cultural studies. For instance, scholars have shown that cultural proximity predicts the popularity of Korean movies and TV dramas among Chinese audiences [28,29] and Asian films among Malaysian audiences [10,30]. Straubhaar's [20] argument also provides a theoretical underpinning that enables an assessment of the extent to which Korean dramas are culturally acceptable to other Asian countries [11].…”
Section: Cultural Proximitymentioning
confidence: 99%